An Electronic Equipment for Monitoring, Detection and Warning of Pitch Motion of Vehicle Drivers - Alzamora, Luis (2023)
Long and monotonous journeys during the transport of goods can generate tiredness and/or fatigue in the driver, generating a potential vehicle accident where the driver can enter a state of micro-sleep, losing control of the vehicle for a period of time. Within the state of the art, it is observed that most of the solutions have as their fundamental axis the analysis of the ocular muscle, being these vulnerable to the variation of light intensity and facial accessories that the driver can use. On the other hand, other studies analyze EEG signals being intrusive and disturbing the driving skills of the driver. This work presents a driver fatigue monitoring system based on the angular movement of the head, the main characteristic prior to the state of micro-sleep, located in a safety helmet. To do this, an analysis of the angular movement of the driver’s head is carried out, thus avoiding the use of cameras, potential lighting problems and intrusive driving disturbances. The device will detect the nodding symptom and will issue an auditory alert with a message via Telegram to a third party to alert the presence of driver fatigue with an error rate of less than 22%, having as auditory alert response time a period of 500 ms equivalent to the distance of 8 m if the vehicle moves at 60 km/h. The validation was carried out by comparing the angles between the device located in the helmet and a reference accelerometer.